Regulasi Emosi dan Dukungan Sosial: Sebagai Prediktor Ide Bunuh Diri Mahasiswa - Syafira Triesna Adinda; Endang Prastuti (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This study aims to know the effect of emotion regulation and social support towards suicidal ideation on college students. This research was based on preliminary data, which showed suicidal ideation that arose among college students. The subject of this study was 210 students of the State University of Malang. This study used descriptive-correlational research. The instrument used in this study was adapted from several measuring devices. There is Emotion Regulation Questionnaire (ERQ) developed by Gross, Interpersonal Support Evaluation List (ISEL) designed by Hoberman & Cohen, and the Suicidal Ideation Questionnaire (SIQ) developed by PAR, Inc (Psychological Assessment Resource), which refers to the scale that was developed by Reynolds. The results show that (1) there is an effect of emotion regulation towards suicidal ideation with t-count value < 0.05 or by 0.000 (2) there is an effect of social support towards suicidal ideation with t-count value < 0.05 or by 0.008 (3) there is an effect of regulation emotion and social support towards suicidal ideation with f-count value < 0.05 or by 0.000, and 39.62% effective contribution. Based on these results, it can conclude that social support and emotional regulation influence the emergence of suicidal ideation in students.